An Analysis of Administrative Staff Performance at Universitas Negeri Manado - Youwlanda Wulan Nofita Pangkey; Herry Sumual; Joulanda A.M. Rawis; Lenny Leorina Evinita (JR Education, 2026)
This study aims to analyze the influence of the work environment, work engagement, and quality of work life on employee performance at Manado State University. The study employs a quantitative approach using multiple regression analyses to examine both partial and simultaneous effects of the variables. The results indicate that the work environment and work engagement have a positive and significant effect on employee performance, with work engagement emerging as the most dominant factor. Meanwhile, quality of work life also shows a positive effect, although its contribution is relatively small. Simultaneously, all three variables significantly influence employee performance; however, in the partial analysis, only the work environment and work engagement remain significant. These findings suggest that improvements in employee performance are more strongly influenced by the level of work engagement and a conducive work environment. Therefore, organizations should prioritize strategies that enhance employee engagement and foster a supportive work environment to achieve optimal performance.